Mental Health Impact of the Deepwater Horizon Oil Spill Among Wives of Clean-up Workers. Issue 4 (July 2015) - Rung, Ariane L.; Oral, Evrim; Fontham, Elizabeth; Harrington, Daniel J.; Trapido, Edward J.; Peters, Edward S.
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.